Hmx: an evolutionary conserved homeobox gene family expressed in the developing nervous system in mice and Drosophila - Wang, WD; Lo, Patrick; Frasch, Manfred; Lufkin, Thomas (Mechanisms of Development, 2000)
Three homeobox genes, one from Drosophila melanogaster (Drosophila Hmx gene) and two from mouse (murine Hmx2 and Hmx3) were isolated and the full-length cDNAs and corresponding genomic structures were characterized. The striking homeodomain similarity encoded by these three genes to previously identified genes in sea urchin, chick and human, as well as the recently cloned murine Hmx1 gene, and the low homology to other homeobox genes indicate that the Hmx genes comprise a novel gene family. The widespread existence of Hmx genes in the animal kingdom suggests that this gene family is of ancient origin. Drosophila Hmx was mapped to the 90B5 region of Chromosome 3 and at early embryonic stages is primarily expressed in distinct areas of the neuroectoderm and subsets bf neuroblasts in the developing fly brain. Later its expression continues in rostral areas of the brain in a segmented pattern, suggesting a putative role in the development of the Drosophila central nervous system. During evolution, mouse Hmx2 and Hmx3 may have retained a primary function in central nervous system development as suggested by their expression in the postmitotic cells of the neural tube, as well as in the hypothalamus, the mesencephalon, metencephalon and discrete regions in the myelencephalon during embryogenesis. Hmx1 has diverged from other Hmx: members by its expression in the dorsal root, sympathetic and vagal nerve (X) ganglia. Aside from their expression in the developing nervous system, all three Hmx genes display expression in sensory organ development, and in the adult uterus. Hmx2 and Hmx3 show identical expression in the otic vesicle, whereas Hmx1 is strongly expressed in the developing eye. Transgenic mouse lines were generated to examine the DNA regulatory elements controlling Hmx2 and Hmx3. Transgenic constructs spanning more than 31 kb of genomic DNA gave reproducible expression patterns in the developing central and peripheral nervous systems, eye, ear and other tissues, yet failed to fully recapitulate the endogenous expression pattern of either Hmx2 or Hmx3, suggesting both the presence and absence of certain critical enhancers in the transgenes, or the requirement of proximal enhancers to work synergistically. (C) 2000 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Hmx; homeobox; Drosophila; central and peripheral nervous system; embryogenesis; inner ear